STATIC FRICTION COEFFICIENT MODEL OF JOINT SURFACES CONSIDERING ASPERITIES INTERACTION AND SUBSTRATE DEFORMATION (MT) - XU YongTai; ZHANG XueLiang; ZHAO HaiLu (Jixie qiangdu)
A statistical model of static friction factor of joint surfaces was deduced, which was more in line with the actual situation and takes into account the interaction of asperities and the deformation of the substrate. Based on the contact load model of joint surfaces considering the interaction of asperities and the deformation of the substrate, the statistical model of the static friction factor of joint surfaces considering the interaction of asperities and the deformation of the substrate was deduced according to the definition of the static friction coefficient of joint surfaces. The parameters of joint surfaces measured by the experiment are substituted into the model for simulation, and it is found that the static friction coefficient of joint surfaces considering the asperities interaction and the substrate deformation is larger than that without considering the asperities interaction and the substrate deformation. The influence of the asperities interaction and the substrate deformation decreases with the increase of the dimensionless normal contact load and decreases with the decrease of the dimensionless distance of joint surfaces, and increases with the decrease of the root mean square of the profile height. The simulation results of the model are compared with the experimental data of the static friction factor. The results show that the static friction coefficient of joint surfaces considering the asperities interaction and the substrate deformation is closer to the experimental data, which shows that the model is correct.